THE IMPLEMENTATION OF PHYSICAL EDUCATION, SPORT AND HEALTH LEARNING THROUGH SPORTS GAME IN BUILDING PRIMARY STUDENTS’ CHARACTERS - Pajar Anugrah Prasetio; Yuniarti Yuniarti; Febby Fajar Nugraha (IKIP Siliwangi, 2019)
This research aimed to investigate the implementation of physical education, sport and health learning through sports game in building primary students’ characters. The method employed in this research is qualitative descriptive. The subjects of this research were five graders and physical education teachers at SDN 1 Awirarangan, SDN 2 Awirarangan, SDN 1 Karangtawang, and SDN 2 Karangtawang, Kuningan, West Java. The data was taken interactively and continuously. The main instruments of this research were observation, interview and documentations. The data were analyzed in accordance with the frameworks proposed by Miles and Huberman which were data collection, data reduction, data presentation, drawing conclusion and verification. The result showed that learning physical education through sports game is a media that can be used to build students’ characters. Through sports game, someone could gain self-control and work together very well. Values like responsible, honest, brave, cooperative, confident, tolerant, mutual respect, religious, polite, wisely accept victory and defeat could be gained through the implementation of sports game. To sum up, the implementation of physical education through sports game is an alternative media to build primary students’ characters.Key words: Physical education, Sports game, Character education